Appreciative inquiry approaches to organizational transformation - Bhattachary, Sudipto, 1969-; Chakraborty, Tanusree (Advances in human resources management and organizational development (AHRMOD) book series., 2020)
"This book examines the need for performance development in organizations and describes some of the common challenges faced by companies"--